Prevalence of nosocomial infections and anti-infective therapy in Benin: results of the first nationwide survey in 2012 - AHOYO, THEODORA ANGÈLE; Bankolé, Honoré S. (My University, 2014)
Background: Data on nosocomial infections in hospitals in low-income countries are scarce and often inconsistent. The objectives of this study were to estimate the prevalence of nosocomial infections and antimicrobial drug use in Benin hospitals. Methods: All hospitals were invited to participate in the first national point prevalence study conducted between 10–26 October 2012 using the protocol developed by the “Hospitals in Europe Link for Infection Control through Surveillance” (HELICS) project. Infection prevalence rates and the proportion of infected patients and exposure to antimicrobials were assessed. Results: Overall, 87% (39/45) of hospitals participated. Of 3130 inpatients surveyed, 972 nosocomial infections were identified among 597 patients, representing an overall prevalence of infected patients of 19.1%. The most frequent infections were related to the urinary tract (48.2%), vascular catheter use (34.7%), and surgical site (24.7%). 64.6% of patients surveyed were treated with antibiotics, including a significant proportion (30%) of non-infected patients and a high proportion of self-medication (40.8%). Resistance of leading nosocomial pathogens to antimicrobials included methicillin-resistance (52.5%) among Staphylococcus aureus, vancomycin resistance among enterococci (67.5%), cefotaxime resistance among Escherichia coli (67.6%), and ceftazidime resistance among Acinetobacter baumannii (100%) and Pseudomonas aeruginosa (68.2%). Conclusions: Benin has high nosocomial infection rates and calls for the implementation of new national infection control policies. Patient safety education and training of all individuals involved in healthcare delivery will be critical to highlight awareness of the burden of disease. The high use of antimicrobials needs to be addressed, particularly their indiscriminate use in non-infected patients.
Keywords: Nosocomial infection; Prevalence; Antimicrobial resistance; Co-morbidity; Antibiotic use; Infection; control; National surveillance; Surveillance; Africa; Low-/middle-income countries